2016
DOI: 10.1016/j.ymeth.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human RNA editing sites: A historical perspective

Abstract: A-to-I RNA editing is an essential gene regulatory mechanism. Once thought to be a rare phenomenon only occurring in a few transcripts, the emergence of high-throughput RNA sequencing has facilitated the identification of over 2 million RNA editing sites in the human transcriptome. In this review, we survey the current RNA-seq based methods as well as historical methods used to identify RNA editing sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 60 publications
5
59
0
Order By: Relevance
“…Statistical survey of these A-to-I editing sites indicated that the majority of them were in introns, intergenic regions, or 3' UTRs ( Fig. 1A & Table S1 in Additional file 2), which is consistent with the data from the popular RNA editing databases, such as RADAR and REDIportal (2,3,6).…”
Section: High Concordance Of Adar1 Binding Sites With A-to-i Editing supporting
confidence: 82%
See 1 more Smart Citation
“…Statistical survey of these A-to-I editing sites indicated that the majority of them were in introns, intergenic regions, or 3' UTRs ( Fig. 1A & Table S1 in Additional file 2), which is consistent with the data from the popular RNA editing databases, such as RADAR and REDIportal (2,3,6).…”
Section: High Concordance Of Adar1 Binding Sites With A-to-i Editing supporting
confidence: 82%
“…Most of A-to-I editing sites are detected in poorly annotated and non-conserved genomic regions, such as introns, intergenic regions (IGRs), and 3' UTRs (5,6). Moreover, RNA editing events are co-transcriptional and rarely happen on mature mRNAs (19).…”
mentioning
confidence: 99%
“…(Desrosiers et al 1974;Perry and Kelley 1974;Dubin and Taylor 1975), technological barriers hindered research into the presence and specific distribution of modified nucleosides within messenger (m)RNAs and other ncRNAs. This changed when next generation sequencing methods were adapted, first to detect RNA editing events, reviewed in (Ramaswami and Li 2016), and soon after to map 5methylcytosine (m 5 C) and N6-methyladenosine (m 6 A) in a transcriptome-wide fashion (Dominissini et al 2012;Meyer et al 2012;Squires et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and importance of A-to-I RNA editing have been illuminated in recent years largely owing to the rapid adoption of high-throughput sequencing technologies 11,12 . Separate laboratories have examined the RNA editome across many tissues or developmental stages in human and other mammals 1317 .…”
mentioning
confidence: 99%